Tuberculosis Associated Chylothorax: A Case Report - Niharika Malego; Ranjan Sapkota; Aakriti Sharma; Pratikshya Thapaliya (Respirology Case Reports)
ABSTRACT Chylothorax is the accumulation of chyle in the pleural cavity. Tuberculosis is one of its rarest causes. Diagnosis of chylothorax can be made by evaluation of triglycerides concentration in pleural fluid. It is primarily managed medically but surgery is indicated when the patients fail to improve after a trial of medical management. Here, we present a case of a 28‐year man who developed chylothorax while undergoing anti‐tuberculous treatment (ATT). After failing initial medical management, he underwent thoracic duct ligation with good result.